STRATEGI MANAJEMEN PEMASARAN DIGITAL UNTUK MENINGKATKAN DAYA SAING UMKM DI ERA EKONOMI DIGITAL - Permana Angga Ade; Abdul Wahid; Dedy Wijaya Kusuma; Ahmad Sauqi; Mustofa; Wasana Sinrungtam (Fakultas Ekonomi dan Bisnis Universitas Pancasila Jakarta, 2026)
This research aims to examine effective digital marketing management strategies to enhance the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in the digital economy. Using a mixed-methods approach (qualitative and quantitative), it identifies best practices and obstacles MSMEs face in implementing digital marketing. The findings reveal that digital marketing, especially social media, significantly boosts MSME competitiveness. However, constraints like limited budgets, low digital literacy, and inadequate human resources hinder its optimization. Practical training, gradual budget allocation, and government support are needed to improve the effectiveness of MSMEs' digital marketing strategies.